1979
DOI: 10.1017/s0043174500046014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Soil Moisture, Temperature, and Compaction on the Germination and Emergence of Downy Brome (Bromus tectorum)

Abstract: The influence of soil moisture stress, temperature, and bulk density on the germination and seedling emergence of downy brome (Bromus tectorumL.) was investigated in the laboratory. Reductions in soil matric potential from -2 to -16 bars markedly reduced the percentage and rate of emergence. Seedling emergence was better at constant than at alternating temperatures. At high matric potentials, the rate of emergence was accelerated by warmer soil temperature (20 C), while at very low matric potentials, the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 24 publications
3
26
0
Order By: Relevance
“…Thill et al (1979) concluded that compaction is a major factor determining its successful establishment, and Beckstead and Augspurger (2004) demonstrated that disturbances that reduce soil compaction increases its biomass and density. However, neither of these studies assessed the effect of altered soil compaction on B. tectorum relative to native plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Thill et al (1979) concluded that compaction is a major factor determining its successful establishment, and Beckstead and Augspurger (2004) demonstrated that disturbances that reduce soil compaction increases its biomass and density. However, neither of these studies assessed the effect of altered soil compaction on B. tectorum relative to native plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Given interference from neighboring cheatgrass, seedling establishment and recruitment into persisting Idaho fescue populations is more probable if germination is rapid (Weiner 1985, Mithen et al 1984). However, because cheatgrass seeds may begin germinating in a single day (Goodwin 1993, Thill et al 1979, and because 5.8 to 9 days passed before Island Idaho fescue germinated, even seedlings from the undisturbed site have little chance of successfully competing with cheatgrass. These data suggest that on alien invaded sites, seedlings from the undisturbed site have a better chance of establishing than do seedlings from disturbed sites.…”
Section: Discussionmentioning
confidence: 99%
“…Cheatgrass germinates more rapidly than Idaho fescue (Doescher et al 1985, Thill et al 1979), so cheatgrass was planted 4 days after Idaho fescue to synchrozine emergence. Seedlings were grown in a greenhouse in a double tube assembly: a soil-filled glass root tube (51 mm X 122 cm) and a black plastic pipe of slightly larger diameter which protected the root tube from breakage and excluded light.…”
Section: Growth and Allocation Experimentsmentioning
confidence: 99%
“…Soil temperatures above 30 0C largely prevent germination during most of summer even when soil moisture is available (Hulbert 1955). Yet germination is not confined to saturated soil; germination may exceed 45% even when the soil matric potential is -1.65 MPa (-16.5 bar) (Thill, Schirman & Appleby 1979). The frequency and amount of rainfall during the rest of September and October are erratic; 30-day droughts are common (Fig.…”
Section: Recruitmentmentioning
confidence: 99%